Innovative computer technologies as an implementer of active methods of training; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Efremova O. N. Oksana Nikolaevna; Ivanova T. O. Tatyana; Plotnikova I. V. Inna Vasilievna; Chaykovskaya O. N. Olga (2016, 2016)
Title screen